Buccal mucosal graft urethroplasty in men—risk factors for recurrence and complications: a third referral centre experience in anterior urethroplasty using buccal mucosal graft - Spilotros, Marco; Sihra, Neha; Malde, Sachin; Pakzad, Mahreen H.; Hamid, Rizwan; Ockrim, Jeremy L.; Greenwell, Tamsin J. (Translational Andrology and Urology, 2017)
Background: Urethral stricture disease is a challenging condition to treat and several approaches including direct visual internal urethrotomy (DVIU) and anastomotic or augmentation urethroplasties based on the use of flaps and graft have been reported. The aim of this study is to determine risk factors for stricture recurrence and complications in patients having buccal mucosal graft (BMG) urethroplasty for anterior urethral stricture under a single surgeon in a third referral centre in UK. Methods: We conducted a retrospective review of a prospectively gathered database of 128 patients having various forms of BMG urethroplasty between 2001 and 2015. Success and failure in terms of stricture recurrence, patient demographics, stricture aetiology and anatomy, and the adverse outcomes of: post-micturition dribbling (PMD), erectile dysfunction (ED) >12 months and complications were recorded in order to determine risk factors for recurrent stricture and complications. Results: The mean age of all patients was 42.8 years (range, 16–74 years). Average follow-up was 45 months (range, 3–159 months). The total re-stricture rate was 19% (24 men). PMD was reported in 16% (n=20) and ED in 12.5% (n=16). All ED was none organic and responded to oral PDE5 inhibitor treatment. Post-operative complications were reported in 16 patients (12.5%). The most frequent complications recorded were urinary fistula (n=4; 3.1%), graft contracture (n=4; 3.1%) and graft failure (n=4; 3.1%), all reported after penile urethroplasty. Univariate analysis indicated that age at surgery, stricture length, site and aetiology were all significant risk factors for stricture recurrence. On multivariate analysis penile site was the only significant independent variable for restricture. Conclusions: BMG urethroplasty represents a reliable therapeutic option for patient with urethral strictures with a success rate of 81% at 45 months of follow-up. Complications are more common in complex stricture of the penile urethra. On multivariate analysis penile site was the only significant independent variable for re-stricture.